PERANCANGAN SISTEM INFORMASI KETERSEDIAAN BANGSAL DI RUMAH SAKIT MENGGUNAKAN METODE WATERFALL GUNA MENUNJANG TATA KELOLA MANAJEMEN RUMAH SAKIT - Aulia Abdalla Maslyta; Isnawan Ardiansyah Fajar; Yuda Syahidin; Erix Gunawan; Neneng Yuniarti (LPSDI Bina Patria, 2023)
The Background of this study focuses on hospitalization registration activities in the hospital, one of those is the process of providing wards in the hospital that are still done manually so that it affects the quality of services in the hospital and also obstructing the process of allocating patients who will be cared for. The purpose of this study is to create a wards availability information system in the hospital, where this information system design can help medical record staff in providing wards availability information and then accelerating service time to patients who will be treated so as to reduce the accumulation of patients in the emergency room. The method used by the author in this design is the Waterfall Method, and the results of this study indicate that this information system design can reduce delays in patient service in hospitals so as to improve the quality of service in hospitals.